Hydrochloric acid leaching behavior of metals from non-magnetic fraction of Pb dross. Issue 6 (2nd November 2019) - Choi, Sanghyeon; Yoo, Kyoungkeun; Alorro, Richard Diaz
ABSTRACT: The leaching behaviors of tin (Sn), antimony (Sb), iron (Fe), and lead (Pb) from non-magnetic fraction of Pb dross, which was obtained from magnetic separation process to remove As components, were investigated using HCl solution. The leaching efficiencies of Sn, Fe, and Pb increased with increasing agitation speed, temperature, and HCl concentration and with decreasing pulp density, but Sb was dissolved only in the 3 and 5 M HCl solutions. The leaching efficiencies of metals increased to 100% in the 5 M HCl solution at 400 rpm and 70°C with 1% pulp density within 120 min. In the case of leaching test with 1 M HCl, Sb components could be recovered as leach residue. After leaching test, Pb could be recovered as PbCl2 from the solution by lowering temperature. Tin ions were extracted selectively by solvent extraction with tri-butyl phosphate, remaining Fe and Pb ions in the solution. The process consisting of HCl leaching, precipitation, and solvent extraction recovers successfully Sb, Pb, and Sn from non-magnetic fraction of Pb dross.